PERTANGGUNGJAWABAN PIDANA PEMILIK ANGKUTAN ATAU TRUK TERHADAP KECELAKAAN LALU LINTAS YANG DIAKIBATKAN KETIDAKLAIKAN ANGKUTANNYA - Alfattah, Bagas Maulana (Jurnal Perspektif Hukum, 2024)
Traffic accidents are often caused by human factors and transportation inadequacies. Although there are regulations related to roadworthiness testing of motorized vehicles such as trucks, public awareness of the law and law enforcement is still not optimal. This results in unfit trucks continuing to operate and potentially causing accidents. This study aims to examine the legal regulation of traffic accidents due to unseaworthiness of transportation, criminal liability of transportation or truck owners for accidents, and solutions to overcome the increase in traffic accidents. The research method used is normative legal research with a descriptive approach. The findings of this research are two main regulations that regulate criminal acts of traffic accidents, namely the Criminal Code (KUHP) and Law Number 22 of 2009 concerning Road Traffic and Transportation (UULLAJ). The criminal responsibility of the driver of a vehicle that causes death in a traffic accident in Article 359 of the Criminal Code is imprisonment for a maximum of five years or confinement for a maximum of one year, can also be given criminal sanctions as stipulated in Law No. 22 of 2009 concerning Road Traffic and Transportation articles 310, 311 or 312. Solutions to reduce traffic accidents due to transportation unfitness include preventive measures, such as increasing public awareness, and repressive measures, such as law enforcement by law enforcement officials.